Pengaruh Model Pembelajaran Direct Learning Terhadap Kemampuan Diagnosis Kerusakan Kendaraan pada Pembelajaran Teaching Factory di SMK - Satrio Nugroho; Dwi Jatmoko; Mike Elly Anitasari; Widiyatmoko Widiyatmoko; Muklis Muklis (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study aims to analyze the effect of direct learning on engine components toward students' vehicle diagnostic abilities in vocational education. Employing a quantitative approach with an ex post facto design, the sample consisted of 80 students selected using simple random sampling from a population of 100 students. Data were collected using validated and reliable questionnaires. The data analysis techniques included descriptive statistics, classical assumption tests, and simple linear regression analysis. The results show that direct learning has a positive and significant effect on students’ vehicle diagnostic abilities, with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.264. This indicates that direct learning contributes 26.4% to the improvement of students' diagnostic abilities. The findings emphasize the importance of practical, hands-on learning approaches in vocational education. These approaches not only enhance students' understanding of automotive theory but also improve their diagnostic skills. The study highlights that systematic learning and direct interaction with engine components are key factors in developing students' competencies, making them more effective in real-world vehicle diagnostics.